Pengaruh Hypnobirthing terhadap Tingkat Kecemasan Ibu Hamil Trimester III dalam Persiapan Persalinan di Klinik Sahabat Bumil - Rosmala Kurnia Dewi; Anggita Septyani Permatasari (LPPM AN NUUR, 2025)
Background: Anxiety in third trimester pregnant women (TM III) is common and linked to negative maternal outcomes. As delivery approaches, anxiety levels increase, particularly regarding labor readiness. Hypnobirthing is a non-pharmacological relaxation technique that has been proven effective in reducing anxiety in preparation for childbirth. Purpose: To determine the effect of hypnobirthing on anxiety levels in third trimester pregnant women in preparation for childbirth at the Sahabat Bumil Clinic. Method: Pre-experimental design with one group pretest-posttest approach. Total sampling of 25 TM III pregnant women (January–June 2024). Anxiety measured using Hamilton Anxiety Rating Scale (HARS). Data analyzed using paired sample t-test. Results: Prior to intervention, 60.0% of respondents experienced moderate anxiety, 12.0% severe, and 8.0% very severe anxiety in facing delivery. Post-intervention, 64.0% had mild anxiety and 12.0% were anxiety-free. Paired t-test showed P value = 0.004 (<0.05), mean anxiety score decreased from 2.84 (SD=0.746) to 2.32 (SD=0.476). Conclusion: Hypnobirthing significantly reduces anxiety levels in TM III pregnant women in preparation for childbirth. It is recommended as a non-pharmacological evidence-based intervention in antenatal midwifery care.